THE PATHOGENETIC ASPECTS OF PARKINSON'S DISEASE AND POSSIBLE WAYS OF THEIR CORRECTION - N. M. Buchakchyiska; V. I. Maramukha; I. V. Maramukha (Сучасні медичні технології)
Purpose of the study. The purpose of the work is to summarize the data available in the literature regarding the role of shock proteins, in particular the HSP 70 protein, in the mechanisms of endogenous neuroprotection and neurodegradation in Parkinson's disease (PD). The article also aims at determining the possible pathogenetic stages of the disease development and the place of mitochondrial dysfunction, apoptotic and antiapoptotic systems in these processes. The modulation of PD MPTP model can help to identify possible ways of influencing the pathogenetic mechanisms of neurodegenerative changes in structures of the extrapyramidal system by stimulating the processes of neuroprotection and slowing of neurodegradation owing to inducing protein level synthesis. After statistical processing of the obtained results, one can interpolate the obtained data on idiopathic PD in the population by matching the relevant neurodegenerative process markers found in the experiment with indicators in PD patients. As a result, it may hypothetically be possible to develop the use of personalized pathogenetic therapy for PD.